MENENTUKAN PROBABILITAS QUALITAS LULUSAN PROGRAM STUDI MENGGUNAKAN LOGISTIC REGRESSION - Maxsi Ary; Slamet Risnanto (Jurnal Informatika, 2014)
Abstract – Human resources (HR) is one of the success factors in the economic field, namely how to create a human resources (HR) qualified and have the skills and highly competitive in the global competition. Educational level of the labor force that is still relatively low. The structure of education of the workforce is still dominated Indonesian basic education which is about 63.2%. The issue raised is to determine the probability of a program of study (whether or not) to see some of the ratio of the number of graduates by the number of students per class, the amount of quota size class (large or small) using logistic regression models. Data were obtained from a search result based on the amount of data the study program students and graduates in 2010 Data processing using SPSS. The results of the analysis by assessing model fit and the results will be given for each model fit. Starting with the hypothesis for assessing model fit, statistical -2LogL, Cox and Snell's R Square, Hosmer and Lemeshow's Goodness of Fit Test, and the classification table. The results of the analysis using SPSS as a tool aimed at measuring quality of graduate courses at a university, college, or academy, whether or not based on the ratio of the number of graduates and class quotas. Keywords: Quota Class, Probability, Logistic Regression Abstrak – Sumberdaya manusia (SDM) adalah salah satu faktor kesuksesan dalam bidang ekonomi, yaitu bagaimana menciptakan sumber daya manusia (SDM) yang berkualitas dan memiliki keterampilan serta berdaya saing tinggi dalam persaingan global. Tingkat pendidikan angkatan kerja yang ada masih relatif rendah. Struktur pendidikan angkatan kerja Indonesia masih didominasi pendidikan dasar yaitu sekitar 63,2%. Persoalan yang dikemukakan adalah menentukan probabilitas sebuah program studi (baik atau tidak) dengan melihat beberapa rasio jumlah lulusan dengan jumlah mahasiswa per angkatan, ukuran besarnya kuota kelas (besar atau kecil) menggunakan model logistic regression. Data diperoleh dari hasil penelusuran data program studi berdasarkan jumlah mahasiswa dan lulusan pada tahun 2010. Pengolahan data menggunakan SPSS. Hasil analisis dengan menilai model fit dan akan diberikan hasilnya untuk setiap model fit. Dimulai dengan hipotesis untuk menilai model fit, statistic -2LogL, Cox dan Snell’s R Square, Hosmer and Lemeshow’s Goodness of Fit Test, dan tabel klasifikasi. Hasil analisis menggunakan SPSS tersebut bertujuan sebagai alat pengukuran qualitas lulusan program studi di suatu Universitas, Perguruan Tinggi, maupun Akademi, baik atau tidaknya berdasarkan rasio jumlah lulusan dan quota kelas. Kata Kunci: Kuota Kelas, Probabilitas, Logistic Regression